Quality and fatty acid profile of high and low value cuts of Barbari goat meat - RAJKUMAR, V; VERMA, ARUN K; DAS, ARUN K; KUMAR, BRIJESH; APURV, S; KUMAR, MAHESH (The Indian Journal of Animal Sciences, 2015)
Quality characteristics and fatty acid profile of muscles from high (Longissimus dorsi) and low value (Supra spinatus) goat meat cuts were investigated followed by comparison of various physicochemical properties and fatty acid profile. Nuggets were prepared with meat from these cuts and their quality and fatty acid profile were also compared. Fat and salt soluble proteins were significantly higher in muscle from low value (LV) cut while in muscle from high value (HV) water soluble proteins were high. Fatty acid profile of both the muscles did not differ significantly, however, saturated fatty acids were relatively high in LV muscle and unsaturated fatty acids in HV muscle. Ash content in emulsion and moisture level in nuggets were higher in nuggets from LV cut. Significant differences were recorded in some fatty acids composition of the products. Sensory evaluation revealed no significant differences in the various attributes of both the products.